Real Time Retinal Optic Disc Segmentation via Guided filter and Discrete Wavelet Transform. Issue 1 (1st August 2022) - Dash, Sonali; Satish Rama Chowdary, P.; Chakravarthy, V.V.S.S.S.; Gopala Raju, C.V.; Sahu, Gupteswar; Siva Charan, KJN; Umamaheshwar, Y.
Abstract: In the world, glaucoma is the one of the main causes for loosing vision. Optical Coherence Tomography or fundus camera is utilized to capture the optic disc and optic cup images. For the detection of glaucoma and afterwards monitoring the patients, investigation of the head of optic nerve or cup-to-disc ratio (CDR) is an important factor. For computing the CDR value, segmentation of optic disc and optic cup are utilized for the isolation of the relevant parts of the fundus image. Even though ophthalmologists are computing the CDR value physically, however, it limits the identification of glaucoma at the early stage. The accurate value of CDR is hard to find out if the optic cup and optic disc are not well defined properly. Thus, this paper has suggested a combined model of Guided filter and Discrete Wave Transform (DWT) for the enhancement and OD segmentation. Hysteresis thresholding is utilized for the optic cup segmentation. A set of 50 images of 25 patients are obtained from Visakha Eye Hospital, Visakhapatnam, India, is used to verify the performance of the suggested model. The recommended approach is also verified on the glaucoma subset of High-Resolution Fundus (HRF) database. The experimental results of both the databases demonstrate that the CDR value is computed accurately with low computational time.